Off Duty (London : Trades Union Congress General Council, 1937)
1937 1937 1930s 12 pages : illustrations Are you — AS A When you are feeling fit life seems good and your job a pleasure. Whatever comes your way, whether it's work or play, you tackle it with vigour and vim. You win the respect of your superiors, the esteem of your colleagues, and the affection of your patients. Nothing gets you down. Your smile banishes worry, and you face the daily round with eagerness and confidence. or do you LIKE A 292/54.73/2/2